1992
DOI: 10.3109/00365529209165432
|View full text |Cite
|
Sign up to set email alerts
|

IgG Subclass Response toHelicobacter pyloriin Patients with Chronic Active Gastritis and Duodenal Ulcer

Abstract: The IgG subclass response is determined by the type of bacteria producing the infection and by genetic factors of the host. Patients with a Helicobacter pylori infection develop a specific immune response that is mainly of the IgA and IgG class. We measured the IgG subclass response in 20 patients with chronic active gastritis without a history of duodenal ulcer and 20 patients with chronic active gastritis and duodenal ulcer diagnosed by endoscopy and histology. A control group included 20 H. pylori-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
2
17
3
Order By: Relevance
“…As reported by others (23,24), in the present study we also observed that IgG concentration in adults does not permit the discrimination between gastritis and duodenal ulcer. We have no explanation for the observation that the IgG concentration in the sera from females with gastritis was significantly higher than in males with gastritis.…”
Section: Diagnosis Of H Pylori Infection By Cobas Core Elisasupporting
confidence: 73%
“…As reported by others (23,24), in the present study we also observed that IgG concentration in adults does not permit the discrimination between gastritis and duodenal ulcer. We have no explanation for the observation that the IgG concentration in the sera from females with gastritis was significantly higher than in males with gastritis.…”
Section: Diagnosis Of H Pylori Infection By Cobas Core Elisasupporting
confidence: 73%
“…Th1 cells that produce gamma interferon are able to promote the production of IgG2 opsonizing and complement-fixing antibodies. An IgG subclass response to H. pylori in patients with chronic active gastritis and duodenal ulcer was reported by Bontkes et al (5). They indicated that the titers of IgG1 antibodies to the bacteria were raised in patients with H. pylori infection and that the titers of IgG2 antibodies in duodenal ulcer patients were higher than those in gastritis patients.…”
Section: Vol 8 2001mentioning
confidence: 85%
“…Instead, their antibody titres may have been too low for detection. Another possibility is that IgGs other than IgG1 and IgG2 may account for the majority of humoral immunity in these patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, adult duodenal ulcer patients have higher IgG2 titres against whole-cell antigens than gastritis patients [10]. Finally, variations in IgG subclass titres may be due to the age and the fact that different H. pylori isolates can express different subsets of antigens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation